Mutu Pelayanan Kesehatan Puskesmas Pasir Panjang Pasca Akreditasi - Lusia D. I. Fernandez; Yoseph Kenjam; Dominirsep O. Dodo (Universitas Nusa Cendana, 2021)
In order to maintain the quality of health services at the health center running maximally, it is necessary to improve performance and sustainable improvement. The Pasir Panjang Health Center has obtained the